2012
DOI: 10.3844/ojbsci.2012.123.133
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTIVENESS OF CULTURAL PARAMETERS ON THE GROWTH AND SPORULATION OF <i>COLLETOTRICHUM GLOEOSPORIOIDES</i> CAUSING ANTHRACNOSE DISEASE OF MANGO (<i>MANGIFERA INDICA</i> L.)

Abstract: Colletotrichum gloeosporioides causing anthracnose which is a serious post harvest disease in mango accounting for 15-20% loss. The variation in nutritional and physiological characteristics among five isolates of C. gloeosporioides collected from different agro-climatic regions of India was investigated. All the isolates showed differential response in requirements of media, temperature and media pH for growth and sporulation. Malt Extract Agar (MEA) medium was best suited for growth in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
(10 reference statements)
3
4
0
Order By: Relevance
“…These results were in line with the earlier findings of Xiao et al (2004) and Kamle et al (2013). Pandey et al (2012) amplified the genomic DNA from 12 isolates of C. gloeosporioides belonging to different regions by PCR with C. gloeosporioides species-specific primers. All the isolates amplified a uniform DNA fragment of size 450 bp.…”
Section: Field Efficacy Testssupporting
confidence: 91%
“…These results were in line with the earlier findings of Xiao et al (2004) and Kamle et al (2013). Pandey et al (2012) amplified the genomic DNA from 12 isolates of C. gloeosporioides belonging to different regions by PCR with C. gloeosporioides species-specific primers. All the isolates amplified a uniform DNA fragment of size 450 bp.…”
Section: Field Efficacy Testssupporting
confidence: 91%
“…Thiophanate methyl Topsin-M/Roko70WP These results of the present study concedes with the reports of earlier workers who reported effectiveness of the systemic, nonsystemic and combi fungicides such as Prashanth et al, (2008) Gud and Raut (2008) reported that Thiophenate-methyl and Propiconazole were most effective against C. gloeosporioides followed by Hexaconazole and Carbendazim. Patel (2009) and Pandey et al, (2012) studied that among the tested fungicides Tricyclazoles were found to be superior for controlling C. gloeosporioides causes anthracnose of mango. Devamma et al, (2012) reported that among all the six fungicides evaluated against C. gloeosporioides the cause of mango anthracnose, the systemic fungicide Thiophanate-methyl (100 %) and the nonsystemic fungicide Mancozeb (100 %) proved to be effective in inhibiting the mycelial growth of the highly virulent pathogen at 50 ppm and 500 ppm concentrations, respectively.…”
Section: Systemic Non-systemic and Combi Fungicides Against C Gloeosporoidesmentioning
confidence: 99%
“…Devamma et al, (2012) reported that among all the six fungicides evaluated against C. gloeosporioides the cause of mango anthracnose, the systemic fungicide Thiophanate-methyl (100 %) and the nonsystemic fungicide Mancozeb (100 %) proved to be effective in inhibiting the mycelial growth of the highly virulent pathogen at 50 ppm and 500 ppm concentrations, respectively. Similarly, Pandey et al, (2012) studied the effect of different fungicides on the control of C. gloeosporioides causes anthracnose of mango. Among the tested fungicides Tricyclazoles were found to be superior for controlling the incidence of pathogen and Saju et al, (2012) reported the effectiveness of different fungicides against C. gloeosporioides infecting large cardamom, the in vitro tests showed that, the pathogen was highly sensitive to Copper oxychloride 50 WP (0.3 %) followed by Mancozeb 75 WP (0.3 %) and combined formulation of Carbendazim + Mancozeb (12 + 63) WP (0.3 %).…”
Section: Systemic Non-systemic and Combi Fungicides Against C Gloeosporoidesmentioning
confidence: 99%
“…Prashanth et al (2008) reported that among four sys- Gud and Raut (2008) reported that Thiophenate-methyl and Propiconazole were most effective against C. gloeosporioides followed by Hexaconazole and Carbendazim. Patel (2009) and Pandey et al (2012) studied that among the tested fungicides Tricyclazoles were found to be superior for controlling C. gloeosporioides causes anthracnose of mango. At higher concentration (2000 ppm) most of the fungicides viz.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with that of Sudhakar (2000); Prashanth (2007); Patel (2009); Devamma et al (2012) reported that among all the six fungicides evaluated against C. gloeosporioides the cause of mango anthracnose, the systemic fungicide Thiophanate-methyl (100 %) and the non-systemic fungicide Mancozeb (100 %) proved to be effective in inhibiting the mycelial growth of the highly virulent pathogen at 50 ppm and 500 ppm concentrations, respectively. Similarly, Pandey et al (2012) studied the effect of different fungicides on the control of C. gloeosporioides causes anthracnose of mango. Among the tested fungicides Tricyclazoles were found to be superior for controlling the incidence of pathogen and Saju et al (2012) reported the effectiveness of different fungicides against C. gloeosporioides infecting large cardamom, the in vitro tests showed that, the pathogen was highly sensitive to Copper oxychloride 50 WP (0.3 %) followed by Mancozeb 75 WP (0.3 %) and combined formulation of Carbendazim + Mancozeb (12 + 63) WP (0.3 %).…”
Section: Discussionmentioning
confidence: 99%